Local Cooperatives In Adaptation And Survival Amid Global Change And Technological Development - Riky Wildan Hepyliyadi; Evania Salsabila; Nanda Puspita; Nanda Sahmawan; Lita Wulantika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
This research aims to analyze the adaptation strategies of KUD Sarwa Mukti in facing global changes, market challenges, and technological developments. The main focus of the research is how local cooperatives can maintain their relevance and achieve business sustainability amidst constantly changing economic dynamics. The method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews with cooperative management and members, direct observation of operational activities, and analysis of documents such as financial reports and cooperative work programs. The results show that KUD Sarwa Mukti implements several key adaptation strategies, namely diversification of products and services, utilization of digital technology, strengthening partnerships, and improving human resource quality. Diversification is carried out by expanding business from the agricultural sector to savings and loan units and the distribution of basic necessities. Digital technology is utilized for promotion through social media and transaction recording. In addition, partnerships with various parties help expand the cooperative's network and business opportunities. Other important factors are visionary leadership and active member participation. Strong leadership enables fast and precise decision-making, while member involvement ensures that policies made are in accordance with common needs. Cooperative values such as gotong royong are maintained and become a strength in facing changes. In conclusion, KUD Sarwa Mukti is an example of a cooperative that has successfully adapted effectively in the era of disruption and can be a model for other cooperatives in Indonesia in facing the challenges of the times.